Pengaruh Variasi Produk, Promosi Digital, Word Of Mouth, dan Suasana Toko Terhadap Keputusan Pembelian Serta Dampaknya Terhadap Kepuasan Pelanggan pada Toko Garda Elektronik Rantauprapat - Niki Amanda Deswita; Ade Parlaungan Nasution; Siti Lam’ah Nasution (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the influence of product variation, digital promotion, word of mouth, and store atmosphere on purchase decisions and their impact on customer satisfaction at Garda Elektronik Store in Rantauprapat. The research employed a quantitative approach with a sample size of 96 respondents. Data were analyzed using PLS-SEM with the help of SmartPLS software. The results indicate that product variation (X1), digital promotion (X2), and word of mouth (X3) do not have a significant effect on purchase decisions. In contrast, store atmosphere (X4) has a significant effect on purchase decisions. Furthermore, purchase decisions significantly influence customer satisfaction. These findings highlight the importance of store atmosphere in shaping both purchase decisions and customer satisfaction.